37.5k views
3 votes
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Given ⇒ 2(x − 4) + 6x = 9x − 10

Step 1 ⇒ 2x − 8 + 6x = 9x − 10
Step 2 ⇒ 2x + 6x − 8 = 9x − 10
Step 3 ⇒ 8x − 8 = 9x − 10
Step 4 ⇒ 8x − 8x − 8 = 9x − 8x − 10
Step 5 ⇒ 0 − 8 = x − 10
Step 6 ⇒ −8 = x − 10
Step 7 ⇒ −8 + 10 = x − 10 + 10
Step 8 ⇒ 2 = x + 0
Step 9 ⇒ 2 = x
Which step in solving this equation is justified by the Distributive Property?
A) Step 1 ⇒ 2x − 8 + 6x = 9x − 10
B) Step 2 ⇒ 2x + 6x − 8 = 9x − 10
C) Step 3 ⇒ 8x − 8 = 9x − 10
D) Step 4 ⇒ 8x − 8x − 8 = 9x − 8x − 10

Please help!

User Meg Risdal
by
5.8k points

1 Answer

0 votes

Answer:

Explanation:

The distributive prpperty is justified in step 1 where the parenthesis is removed when the number 2 is multiplied by the variable x to get 2x and in the same way by -4 to get -8

User Sam Rogers
by
5.4k points